Experimental Study on the Effects of Stress-Induced Damage on the Microstructure and Mechanical Properties of Soft Rock - Hao Wang; Yong-Yan Wang; Zhuo-Qun Yu; Jian-Guang Li (Advances in Civil Engineering)
After rocks are damaged under stress loading, the changes of their microstructural and mechanical properties are major factors that affect construction safety in geotechnical engineering projects. Studying the microstructures and mechanical behaviors of stress-damaged rocks can help better guide construction and reduce construction risks for geotechnical engineering projects. In this study, a sandstone was first artificially predamaged and then subsequently subjected to scanning electron microscopy (SEM) analysis, computed tomography (CT) scanning, and uniaxial compression testing. Afterwards, the rock microstructures were three-dimensionally (3D) reconstructed, and the pores were classified and characterized based on their diameters. Moreover, the microstructural and mechanical parameters of the rock were subjected to significance analysis. The results showed that as the stress-induced damage (σi) increased, the uniaxial compressive strength (σc) of the soft rock decreased by 13.7–31.8%; as σi increased from 11.2 to 19.6 MPa, the elastic modulus (E) of the soft rock increased by up to 28.8%; and as σi increased beyond 19.6 MPa, there was a significant (22.3%) decrease in E. Stress-induced damage significantly affected the spatial distribution of the pores’ structure of the soft rock. Changes in the spatial structure of the pores led to the formation of cracks. The microstructural parameters of the stress-damaged soft rock were correlated with its mechanical parameters.